Traceability in a supply chain with repeated moral hazard - Saak, Alexander E. (International Food Policy Research Institute, 2012)
Recent food safety events have raised concerns about food traceability in both developed and developing countries. In this paper we study the decision to adopt a traceability system in a supply chain with repeated upstream and downstream moral hazard and imperfect consumer monitoring. In deciding whether to maintain information regarding product origin, firms face a trade-off. On one hand, the downstream firm’s threat to punish upstream shirking is more credible when products are traceable to their firm of origin. On the other hand, the downstream firm has less incentive to collude with a subset of upstream firms to shirk in the provision of quality when it cannot tell whether a product originates from a shirking or non-shirking firm. We show that firms achieve higher joint profits when products are not traceable to upstream suppliers if the cost savings from upstream shirking and the discounted cost savings from downstream shirking are sufficiently similar or the consumer experience is a sufficiently noisy signal of quality.